(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The role of genetic factors in the development of primary open-angle glaucoma (POAG) has been confirmed previously. Activation of oxidative stress with a reduction in the activity of glutathione S transferase (GST) family enzymes is a major mechanism in the pathogenesis of POAG. Since there are substantial population differences in frequencies of GST polymorphisms and there are contradictory reports regarding the association between GST polymorphisms and POAG, we considered it reasonable to investigate these polymorphisms in a Ukrainian population of patients with POAG. Purpose: To investigate the distribution of polymorphic genotypes of GSTP1, GSTM1 and GSTT1 and their associations with the development and progression of POAG. Materials and Methods: One hundred and seventy two patients (344 eyes) diagnosed with POAG were involved into the study. In addition, the control group comprised 98 volunteers (196 eyes) diagnosed with no POAG. Patients were divided into four groups based on the stages of glaucoma identified by Nesterov (2008): Group 1 (mild POAG; 38 patients), Group 2 (moderately advanced POAG; 44 patients), Group 3 (far advanced disease with markedly constricted visual fields; 40 patients), and Group 4 (terminal stage POAG, with developed blindness; 50 patients). The polymorphisms were determined using real-time polymerase chain reaction and TaqMan Mutation Detection Assays (Life Technologies). Statistical analyses were performed using MedStat and MedCalc v.15.1 (MedCalc Software bvba). Results and Discussion: We identified 11 combinations of genetic variants which were significantly different in frequency between patients with POAG and controls and between different groups of patients (χ2=112.63; p=0.00Е-01). In addition, we revealed significant differences in the distribution of genotypes between total patients with POAG and controls (χ2=54.68, p=0.00Е-01). The frequencies of the polymorphisms in the controls were different from those observed in glaucoma patients in Group 1 and Group 2 (p(χ2)=0.001 and p(χ2)=0.003, respectively), and Groups 3 and 4 (p(χ2)= 0.00Е-01). The risk for the development of stage 1 POAG was 15-fold increased in patients exhibiting the combination of GSTP1(Val/Val), GSTM1-null and GSTT1+ genotypes. The combination of GSTP1(Ile/Ile), GSTM1-null and GSTT1-null genotypes was associated with the progression of the disease, with 5.1-fold, 6.6-fold, and 13-fold increased risks for development of stage 2, stage 3 or stage 4 POAG, respectively. The combinations including the ancestral genotype GSTP1(Ile/Ile) with GSTM1 and/or GSTT1 non-null genotypes were found to be protective against progression of POAG. Conclusion: The polymorphic genotypes of GSTP1, GSTM1 and GSTT1 which result in reduced antioxidative activity are essential in both the incidence and progression of POAG. The combinations including the GSTM1 and GSTT1 mutant (null) alleles were found to be pathological, whereas those including the ancestral genotype GSTP1(Ile/Ile) with GSTM1+ and/or GSTT1 + were found to be protective against progression of POAG.